Impact of a pharmacy‐led nursing education on discharge opioid prescribing after kidney transplant. Issue 2 (19th October 2021) - Benken, Jamie; Lichvar, Alicia; Reticker, Anesia; Benedetti, Enrico; Votta Velis, Effrossyni; Campara, Maya
Abstract: A major contributor to the opioid epidemic is prescribing in the postoperative setting. There remains the need for opioid stewardship both postoperatively and upon discharge in kidney transplant recipients. In October 2017, pharmacist‐led education was given to all transplant nursing staff at a single center with the goal of optimizing postoperative pain control through education and empowerment of nurses. Furthermore, the education focus was to advance nursing knowledge, enhance patient assessment, and reform patient education. Clinical pharmacists continued to work with the transplant team to base a patient's discharge analgesia on inpatient analgesia use. This study assessed the impact of the nursing education on discharge analgesic prescribing patterns after kidney transplant admission. Opioid prescribing on transplant discharge was significantly lower after the education (pre 68.3% vs post 11.1%, P <.001). Transplant admission was shortened by 1 day (6 vs 5 days, P = .03). Over time, a significant downtrend in opioid prescribing was observed on discharge from 86.1% in 2015 to 49.6% in 2017 and 8.5% in 2018 ( P <.001). If opioid therapy was required on discharge in the posteducation group, tramadol was predominantly prescribed (7/13 opioid prescriptions, 53.9%). Thus, opioid minimization and pain management using nonopioid analgesic prescribing on discharge are feasible in an adult kidney transplant population with proper nursing collaboration and education.